Avaliação do efeito clínico da terapia de fotobiomodulação com o uso do laser de baixa intensidade em rosácea eritêmato-telangiectásica - Trivelin, Maria Laura de Oliveira de Avelar Alchorne (2016)
Introduction: Rosacea is a disease with chronic evolution, altering periods of improvement and worsening, mainly on the face, caused by an inflammatory process that involves skin vessels and pilosebaceous unit. The disease leads to the development of erythema, with symptoms such as burning, pain, reddening and itching. It should be treated so as to avoid psychological and physical effects, since it has no spontaneous healing and serious progressive evolution. It is considered a real scourge to its patients, many of whom develop a situation of anxiety, depression, frustration, isolation, low self-esteem, among other emotional and psychological problems. Most cases of rosacea can be controlled with drugs although they showed adverse effects. Even if there is no cure, the factors stimulating outbreaks, treating aggravation and sequelae, and preventing relapses after treatment should be avoided. Low-Level Laser Therapy (LLLT) has been used as a therapeutic modality in tissue regeneration, reduction of inflammation, analgesia, and alteration of the immune response as studied by our group. Objective: To evaluate the therapeutic, clinical and qualitative response and perception of patients with erythematotelangiectatic rosacea before and after photobiomodulation therapy in the red (660nm) and infrared (780nm) wavelengths. Methodology: Prospective and longitudinal study with 26 patients divided into 2 groups: G1 – 17 patients treated with LLLT in red (660nm) and G2- 9 patients treated with LLLT in infrared (780nm) and in red (660nm). The parameters for G1 and G2 were: Power (P) = 15mW, Time (T) = 10 s, Fluency (DE) = 3,8J/cm2, Spot size (Ѳ) = 0,025cm2, Energy per point (εpt) = 0,15J/pt, Total Energy (εT) = 5,8 – 9,4J, Irradiance = 0,6W/cm2, continuos wave and application= one time a week. The area to be treated on the face with rosacea and normal facial skin was evaluated with a digital thermometer. The dermatological clinical evolution occurred weekly through signs of local inflammation, such as: erythema, pruritus and skin lesion area, local temperature measurement and photographic follow-up. The cutaneous pH pre and post LLLT were also measured. The patients answered two questionnaires about their perception of the illness (pre and post treatment). There were made 10 weekly sessions with revaluation after the 5th and 10th week of the LLLT application with 6 mo follow up. Results: Both groups studied presented the prevalence of rosacea in women, in a ratio of 3:1 in individuals with Fitzpatrick II and III phototypes, with episodes of more intense flushing in the 3rd and 4th decades. The main signals and symptoms elicited by the patients are classic to rosacea and presented a deep improvement, especially in relation to the rash, burning and itching. The telangiectasia cleared or diminished. The skin temperature with the lesion did not increase more than 1ºC after LLLT and the pH of both the regular and the lesion skin remained within the normality levels (4.5-5.8). The results were the same, according to the clinical evaluation by the dermatology specialists, for both the red and the infrared. Eleven patients who completed the treatment for at least 6 months did not present relapses with well-attenuated signs and symptoms. Conclusion: LLLT was able to reduce the symptoms of erythematotelangiectatic rosacea with no side effects, in a painless and noninvasive way. It was observed attenuation of alodininea (erythema, burning, pruritus), facial edema and telangiectasias post 10 applications of energy-based device. In addition, there was the maximum degree of satisfaction of the patients evaluated by the perception questionnaires, giving them increased self-esteem and improvement in discomfort, anxiety and stress, with cost-effectivenes to these individuals that underwent to the Photobiomodulation.